Guerres et occupation anarchique des espaces urbains en République Démocratique du Congo. Regard sur les blocs RVA et Hewabora dans la ville de Kindu Par - Makinga, Alphonse Sabiti; Alphonse Mbate Lupiki; Innocent Ramazani Mizaba (IJRDO - Journal of Social Science and Humanities Research, 2020)
The migratory fluxes, certainly exercise a considerable pressure on the city in terms of demand of lodging and the fundamental. This situation developed a new fashion of the fundamental occupation clearing on a wild morcelement of the urban and conducted soil to the proliferation of the casual habitats. However, even though the war caused an important occupation of the space of the city of Kindu, it doesn’t constitute some for as much the unique reason. Indeed, the war had only caused the migratory flux. The choice of the space to occupy by the migrants was bound more to the security constraints, provoking a fundamental mess thus. This established article an interrelationship between the war and the anarchical occupation of the urban space in the city of Kindu and precisely in two blocks to know the RVA and Hewa Bora in the city of Kindu